Prevalance of Celiac Disease in Subjects With Diverticular Disease Of The Colon - Mesut Aydın; Serhat Özer; Yaren Dirik; Elif Tuğba Tuncel; Ahmet Cumhur Dülger (Van Tıp Dergisi, 2021)
INTRODUCTION: Celiac disease (CD) is a small bowel malabsorption syndrome that is caused by hypersensitivity to wheat in subjects who have positive HLA haplotypes DQ2 and DQ8. Diverticular disease of the colon (DDC) is saccular dilatations of colon, which is seen mostly in adults older than 40. In this study, we tried to see whether CD is protective for DDC. METHODS: We identified 114 (57 female; the mean age 58+-4.1 years) patients with DDC during the 7-month period from January to October 2018. Age-matched control group (100 subjects; 50 female; the mean age 59+-3.4 years) was selected from subjects without DDC. RESULTS: Among subjects with DDC, only one tested positive for CD serologically (Tissue Transglutaminase - tTTG IgA and G). In control subjects with dyspepsia, 2.8% of subjects tested positive for celiac antibodies. There was a robust difference between groups in terms of TTG Ig A seropositivity (P<0.005, respectively). DISCUSSION AND CONCLUSION: The results indicate an inverse relationship between DDC and CD. These data support that lack of celiac antibodies may have a preventive role for developing DDC. The mechanism of presented finding is still unclear. Further research is needed.